(untitled) (American Journal of Islam and Society, 1994)
The subject of naturalization, which is an integml part of the concept of identity and its related problems, has been an issue in the Muslim world since its filst contacts with western thought, culture, military, and politics. Even though the matter was decided, in practical terms, by the emergence of ethnic and geographic nation-states out of the wreckage of the Ottoman Empire, it remains an open topic at the cultural and academic levels. In fact, whether it is addressed as a challenge, an excuse, or as a means to an end, it remains a major and very sensitive question. As new ethnic and regional Muslim nation-states begin to show signs of instability, the subject grows more complex: it takes on new aspects of identity and affiliation and seeks to discover the best way of ordering relations between the peoples of each region or between them and the (factional, military, or otherwise) elitist governments controlling them. With the stirrings of a new Islamic movement and its members’ belief that Islam represents a viable political alternative, the question of naturalization has become a major challenge to them. In fact, it is often thrown in their faces by their secularist opponents. Thus the question has become instrumental in the current political struggle taking place in the Islamic world. Many Muslim governments cite indigenous non-Muslim minorities as an excuse to deprive their Muslim majorities, who often represent 98 percent of the total population, of the right to be ruled by the Shari’ah. These are the same governments that discredit Islamic movements by viewing their very presence, principles, demands, and objectives as a threat to national unity. To counteract this "threat," then, they promulgate "emergency measures" and suspend constitutional legal codes. Naturalization is the basis of nationalism, which gives identity to the modem state, and may be defined as an affiliation with a geographically defined region. Anyone who traces hisher lineage to that region is subject to all accompanying rights and responsibilities. Thus the bond between them is secular and worldly. The same is true of bonds between states, for they are entirely secular and m e a s d in terms of profit and loss. It is essential that all citizens, regardless of their religious, ethnic or ...